2019
DOI: 10.3892/ijmm.2019.4298
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin alleviates orthopedic implant‑associated infection

Abstract: Implant-associated infection (IAI), a common condition marked by progressive inflammation and bone destruction, is mentally and financially devastating to those it affects, causing severe morbidity, prolonged hospital admissions, significant hospital costs and, in certain cases, mortality. Aspirin, a popular synthetic compound with a history of >100 years, is antipyretic, anti-inflammatory and analgesic. It is the most active component of non-steroidal anti-inflammatory drugs. However, the effects of aspirin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In a paper aiming at investigating anti-virulence properties of diflunisal (a COX-1 selective NSAID) on S. aureus, Hendrix et al (2016) demonstrated that diflunisal protected from osteolysis in a rodent model of S. aureus-induced osteomyelitis. Similar protective effects were also observed with aspirin (also a COX-1 selective NSAID) in a murine model of ODRI (Jiang et al, 2019), thereby suggesting that COX inhibition may prevent infection-induced bone destruction. However, clinical evidence on the effect of NSAID use on fracture healing is limited, with relatively few high-quality studies available.…”
supporting
confidence: 58%
“…In a paper aiming at investigating anti-virulence properties of diflunisal (a COX-1 selective NSAID) on S. aureus, Hendrix et al (2016) demonstrated that diflunisal protected from osteolysis in a rodent model of S. aureus-induced osteomyelitis. Similar protective effects were also observed with aspirin (also a COX-1 selective NSAID) in a murine model of ODRI (Jiang et al, 2019), thereby suggesting that COX inhibition may prevent infection-induced bone destruction. However, clinical evidence on the effect of NSAID use on fracture healing is limited, with relatively few high-quality studies available.…”
supporting
confidence: 58%
“…It has a certain impact on bone metabolism and bone health, promoting osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs), inhibiting adipogenic differentiation of BMSCs, activating osteoblasts and inhibiting osteoclasts. [18][19][20][21][22] It has been found to promote bone formation by inhibiting the expression of inflammatory factors such as IFN-γ and TNF-α. [23][24][25] It may also improve bone marrow microenvironment and enhance immune regulation of BMSCs.…”
mentioning
confidence: 99%
“…In 2019, using a mouse model of orthopedic implant-associated infections ( S. aureus ), researchers demonstrated that treatment with moderate doses of ASA resulted in decreased periosteal reactive bone, osteolysis and osteoclast activation but increased osteoblast activation in implant-associated infections mice, whereas a high dose of ASA aggravated rather than alleviated implant-associated infections [ 80 ].…”
Section: Resultsmentioning
confidence: 99%